2012
DOI: 10.1111/j.2042-7158.2012.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multidose cilostazol on pharmacokinetic and lipid profile of atorvastatin in male Wistar rats

Abstract: Multi-dose administration of CLZ influences the pharmacokinetics and lipid-lowering properties of ATV. Collectively, an apparent interaction between selected drugs was evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The drug is a CYP3A4 substrate, and most of CYP3A4 substrates are P-gp substrates as well (Boyd et al, 2000). Vatsa et al stated that atorvastatin is a P-gp substrate at lower dose and an inhibitor at higher doses (Vatsa et al, 2012). The P-gp substrate activity of atorvastatin was also suggested by some other studies (Williams and Feely, 2002;Wu et al, 2000).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The drug is a CYP3A4 substrate, and most of CYP3A4 substrates are P-gp substrates as well (Boyd et al, 2000). Vatsa et al stated that atorvastatin is a P-gp substrate at lower dose and an inhibitor at higher doses (Vatsa et al, 2012). The P-gp substrate activity of atorvastatin was also suggested by some other studies (Williams and Feely, 2002;Wu et al, 2000).…”
Section: Discussionmentioning
confidence: 73%
“…Vatsa et al reported that atorvastatin is a moderate substrate for CYP P450 and is extensively metabolized via CYP P450-mediated oxidation and phase II glucuronidation both in humans and rats (Vatsa et al, 2012). The drug is a CYP3A4 substrate, and most of CYP3A4 substrates are P-gp substrates as well (Boyd et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies reporting effects of ATV other than reducing cholesterol synthesis in rats have given ATV doses (10 mg/kg) much larger than those prescribed in humans (up to 80 mg/day or <2 mg/kg); in these 10 mg/kg conditions, levels of ATV in rat blood reach 500–1000 nM (Vats et al . ; Kim et al . ), being o‐ATV levels in plasma similar to those of ATV (Crevar‐Sakač et al .…”
Section: Methodsmentioning
confidence: 99%
“…The drug sacs were then placed in individual incubation chambers containing 20 ml of the oxygenated buffer at 37 °C. The P app values, expressed in cm/s, were calculated using the following equation : Papp=dQ/dt/A.Cowhere d Q /d t is the rate of appearance of LPV in the everted gut sac (receiver compartment), C o is the initial concentration of CLZ outside the everted gut sac (donor compartment) and A is the total cross sectional area of tissue.…”
Section: Methodsmentioning
confidence: 99%